2008
DOI: 10.1017/s0007114508894408
|View full text |Cite
|
Sign up to set email alerts
|

Effect of the dietary fat quality on insulin sensitivity

Abstract: Recent evidence shows that specific fatty acids affect cell metabolism, modifying the balance between fatty acid oxidation and lipogenesis. These effects may have important implications in addressing the present epidemic of nutrition-related chronic disease. Intake of dietary saturated and n-6 PUFA have increased while n-3 fatty acid intake has decreased. Obesity, type 2 diabetes and insulin resistance are highly prevalent, and both are strongly related to disorders of lipid metabolism characterized by an incr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
83
1
3

Year Published

2009
2009
2022
2022

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 130 publications
(89 citation statements)
references
References 61 publications
2
83
1
3
Order By: Relevance
“…The PON1 5 ′ region has two sterol responsive element (SRE)-like regions, and sterol regulatory element binding protein 2 (SREBP2) has been shown to bind to the PON1 promoter and increase expression ( 52 ). SREBP2 also upregulates LDLR ; thus, it is possible that the hepatocytes respond to the increased cholesterol load or a correlated elevation, such as that of insulin ( 73 ), by activating SREBP2, which then activates PON1 expression. The putative antiatherogenic dietary fl avonoid quercetin has been shown to increase both PON1 ( 74 ) and LDLR ( 75 ) expression via the SRE pathway.…”
Section: Discussionmentioning
confidence: 99%
“…The PON1 5 ′ region has two sterol responsive element (SRE)-like regions, and sterol regulatory element binding protein 2 (SREBP2) has been shown to bind to the PON1 promoter and increase expression ( 52 ). SREBP2 also upregulates LDLR ; thus, it is possible that the hepatocytes respond to the increased cholesterol load or a correlated elevation, such as that of insulin ( 73 ), by activating SREBP2, which then activates PON1 expression. The putative antiatherogenic dietary fl avonoid quercetin has been shown to increase both PON1 ( 74 ) and LDLR ( 75 ) expression via the SRE pathway.…”
Section: Discussionmentioning
confidence: 99%
“…Several investigations showed that dietary omega-3 FAs may affect glucose metabolism and plasma lipids both in healthy people and patients with metabolic syndrome [251][252][253][254][255][256][257]. Nevertheless, overall the most representative meta-analysis performed in the last decade showed that omega-3 FA supplementation up to 5 g/day consumed for 3 months do not significantly affect insulin sensitivity and glucose homeostasis both in healthy subjects and diabetic patients [258][259][260][261][262].…”
Section: Adverse Effects Of N-3 Polyunsaturated Fatty Acidsmentioning
confidence: 99%
“…The high total and saturated fat intakes of the current sample are of concern, given that fatty acid intake is shown to influence glucose metabolism through the altering of insulin signalling and cell membrane function, with a diet high in saturated fatty acid associated with a decrease in insulin sensitivity when compared with a high monounsaturated Diets of women with polycystic ovary syndrome S Barr et al fatty acid (MUFA) diet (Galgani et al, 2008). Furthermore, a review by Risérus (2008) concluded that saturated and trans fatty acids should be replaced with poly unsaturated fatty acids and MUFAs to confer benefits in terms of improving insulin sensitivity and preventing type 2 diabetes mellitus.…”
Section: Recommendation For the Modification Of Dietary Fat Intakementioning
confidence: 99%